Composite multifunctional lithium metal negative electrode and preparation method and application thereof

By introducing lithium-philic nanoparticle layer and evaporation to form a multifunctional SEI layer, the problems of uneven lithium deposition, interfacial side reactions and insufficient SEI layer performance are solved, and the stability and safety of the lithium-metal negative electrode are significantly improved and the service life of the battery is extended.

CN119725404AActive Publication Date: 2025-03-28TIANFU JIANGXI LAB

Patent Information

Application Number
CN202411891928.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing lithium metal negative electrodes have problems such as uneven lithium deposition leading to dendrite growth, irreversible loss caused by interface side reactions, insufficient SEI layer structure performance and weak interface bonding force of the material, resulting in poor battery stability and safety.

Method used

By introducing a lithium-philic nanoparticle layer, the nucleation overpotential is reduced, the lithium deposition morphology is adjusted, and the lithium conduction homogeneous layer and a multifunctional artificial SEI layer are formed through evaporation to improve the migration efficiency and interface binding force of lithium.

Benefits of technology

Significantly improve the stability and safety of lithium metal negative electrodes, reduce capacity attenuation, extend battery life, improve the ionic conductivity, stability and mechanical properties of negative electrode materials, and reduce the potential risks of thermal runaway and short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725404A_ABST
    Figure CN119725404A_ABST
Patent Text Reader

Abstract

The invention discloses a composite multifunctional lithium metal negative electrode and a preparation method and application thereof, and relates to the technical field of lithium ion batteries. The invention relates to a preparation method of a composite multifunctional lithium metal negative electrode, which comprises the following steps: adding lithium-loving nanoparticles into an N-methyl pyrrolidone solution, fully dispersing, coating on a copper foil, and drying to obtain a lithium-loving nanoparticle layer; cleaning and preheating the surface of the lithium negative electrode; transferring the lithium-loving nanoparticle layer to the lithium foil; evaporating the lithium foil, and depositing on the surface of the lithium foil substrate to form a thin film; and cooling and curing the evaporated lithium foil to obtain the composite multifunctional lithium metal negative electrode. According to the invention, the problems of dendritic crystal growth caused by uneven lithium deposition, irreversible loss caused by interface side reaction, insufficient structural performance of the existing SEI layer and weak material interface bonding force are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite multifunctional lithium metal negative electrode and a preparation method and application thereof. Background Art

[0002] In the ongoing exploration of high-energy-density batteries, lithium metal anodes are considered to be one of the key materials due to their theoretical specific capacity of up to 3860 mAh / g and low electrochemical potential (-3.04 V vs. standard hydrogen electrode), which is of great significance in promoting the innovation of battery technology. However, despite the huge application potential of lithium metal anodes, their practical application still faces a series of complex and urgent challenges.

[0003] First, the non-uniform deposition of lithium metal during the charge and discharge cycle leads to the formation of lithium dendrites, which becomes a major safety hazard. The growth of dendrites not only reduces the utilization of effective lithium, but also penetrates the battery separator, causing internal short circuits, which may trigger thermal runaway, seriously threatening the safety of the battery. Secondly, the interfacial stability problem between lithium metal and the electrolyte cannot be ignored. During the electrochemical reaction, the lithium metal anode is very prone to side reactions in the electrolyte, and the solid electrolyte interface (SEI) layer formed is often unstable. Its uneven thickness, brittleness and low ionic conductivity lead to continuous loss of active lithium and reduced coulombic efficiency. The repeated rupture and reconstruction of the SEI layer aggravates the decline of battery performance. Furthermore, the existing technology has limitations in constructing an ideal SEI layer, and it is difficult to balance the requirements of stability and high conductivity. This limits the long-term cycle performance of the lithium metal anode, which significantly affects the overall energy density and cycle life of the battery. In addition, the deposition and transfer technology of materials is also one of the bottlenecks of current research. Traditional methods make it difficult to ensure the uniformity and stability of the coating, resulting in insufficient interface bonding and material shedding during the cycle process, further deteriorating battery performance.

[0004] In summary, current technologies still face many challenges in improving the stability and safety of lithium metal anodes. In order to achieve safe and efficient application of lithium metal anodes in high energy density batteries, it is urgent to develop new material design strategies and advanced surface treatment technologies to optimize the structure and performance of the SEI layer, inhibit dendrite growth, and enhance interface stability, thereby improving the cycle life and safety of the battery. Summary of the invention

[0005] The technical problem to be solved by the present invention is that the stability and safety of the existing lithium metal negative electrode are poor, and there are also problems such as uneven lithium deposition leading to dendrite growth, irreversible loss caused by interface side reactions, insufficient structural performance of the existing SEI layer and weak material interface bonding force. The purpose is to provide a composite multifunctional lithium metal negative electrode and its preparation method and application, which solves the problems of uneven lithium deposition leading to dendrite growth, irreversible loss caused by interface side reactions, insufficient structural performance of the existing SEI layer and weak material interface bonding force.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a composite multifunctional lithium metal negative electrode, comprising the following steps:

[0008] Adding lithium-philic nanoparticles into N-methylpyrrolidone solution, fully dispersing and coating on copper foil and drying, thereby obtaining a lithium-philic nanoparticle layer;

[0009] Cleaning and preheating the surface of the lithium negative electrode;

[0010] transferring the lithiophilic nanoparticle layer onto lithium foil;

[0011] Evaporating the lithium foil to form a thin film on the surface of the lithium foil substrate;

[0012] The evaporated lithium foil is cooled and solidified to obtain a composite multifunctional lithium metal negative electrode.

[0013] As a possible design, the above-mentioned sufficient dispersion is achieved by adding the lithium-philic nanoparticles into an N-methylpyrrolidone solution and magnetically stirring for 4-6 hours.

[0014] As a possible design, the drying step is specifically to dry the lithium-philic nanoparticle solution coated on the copper foil under vacuum at 60-70° C. for 12-16 hours.

[0015] As a possible design, the above-mentioned transfer of the lithium-philic nanoparticle layer to the lithium foil is specifically to cover the copper foil on the lithium foil so that the lithium-philic nanoparticle layer is in contact with the lithium foil, and press a heavy object on the copper foil. After standing for 10-30 minutes, the copper foil is peeled off and the lithium-philic nanoparticle layer is transferred to the lithium foil.

[0016] As a possible design, the above-mentioned evaporation of lithium foil includes:

[0017] The high ion conductivity material is heated and evaporated, and a lithium foil is placed on the high ion conductivity material for a first evaporation deposition, so as to form a first film on the surface of the lithium foil substrate;

[0018] The inorganic composite material is heated and evaporated, and the evaporated lithium foil is placed on the inorganic composite material for secondary evaporation, and a secondary thin film is deposited on the surface of the lithium foil substrate.

[0019] As a possible design, the heating and evaporation parameters of the above high ionic conductivity material are as follows: vacuum degree is 10 -4 -10 -6 Pa, heating power is 230-270W, evaporation rate is

[0020] As a possible design, the inorganic composite material is made by fully mixing a variety of inorganic materials, including LiF, Li 2 O. Li 2 CO 3 , Li 3 N and Li 2 S.

[0021] As a possible design, the heating and evaporation parameters of the inorganic composite material are as follows: the vacuum degree is 10 -4 -10 - 6 Pa, heating power is 230-270W, evaporation rate is

[0022] In a second aspect, the present invention provides a composite multifunctional lithium metal negative electrode prepared by any of the above methods.

[0023] In a third aspect, the present invention provides an application of a composite multifunctional lithium metal negative electrode prepared by the above-mentioned preparation method in battery materials.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] The present invention introduces a lithium-philic nanoparticle layer, attaches it to the surface of the lithium negative electrode, reduces the nucleation overpotential, adjusts the lithium deposition morphology, and further forms a lithium-conducting homogeneous layer by evaporation to improve the migration efficiency of Li. Finally, by evaporating lithium foil, using high ionic conductivity materials and inorganic composite materials, a multifunctional artificial SEI layer is constructed to improve the binding force with the lithium negative electrode; it can also significantly improve the stability of the lithium metal negative electrode, reduce capacity decay, extend the service life of the battery, and improve the ionic conductivity, stability and mechanical properties of the negative electrode material; at the same time, by reducing dendrite growth and side reactions, the potential risks of thermal runaway and short circuit are reduced, and the overall safety performance of the battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0027] Figure 1 is a flow chart of the preparation method of the present invention;

[0028] Figure 2 It is a schematic diagram of the preparation method of the present invention;

[0029] Figure 3 is the ohmic internal resistance diagram of Experimental Example 1 of the present invention;

[0030] Figure 4 This is the interface impedance diagram of Experimental Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0032] Due to the poor stability and safety of existing lithium metal negative electrodes, there are also problems such as uneven lithium deposition leading to dendrite growth, irreversible losses caused by interface side reactions, insufficient structural performance of the existing SEI layer, and weak material interface bonding. The present invention provides a method for preparing a composite multifunctional lithium metal negative electrode, which reduces the nucleation overpotential and adjusts the lithium deposition morphology by introducing a lithium-philic layer. Further evaporation forms a lithium-conducting homogeneous layer to improve the migration efficiency of Li. Finally, an inorganic composite material is used to construct a multifunctional artificial SEI layer. This method can effectively improve ionic conductivity, stability, and mechanical properties, and solve problems such as dendrite growth and poor safety.

[0033] A method for preparing a composite multifunctional lithium metal negative electrode, referring to Figure 1-2 , including the following steps:

[0034] S1. Adding lithium-philic nanoparticles to N-methylpyrrolidone (NMP) solution, fully dispersing and coating the solution on copper foil, and then drying the solution to obtain a lithium-philic nanoparticle layer.

[0035] By coating the lithium-philic nanoparticles on the copper foil, since the copper foil has good chemical stability and is not easy to adhere to lithium metal, it can be ensured that no copper foil impurities will remain when the lithium-philic nanoparticle layer is subsequently separated.

[0036] By attaching lithium-philic nanoparticles to the surface of the lithium negative electrode, a lithium-philic nanoparticle layer is formed. The lithium-philic layer reduces the potential barrier required for lithium metal nucleation by providing active sites and enhancing interface affinity; it can optimize the surface structure of the material, thereby improving lithium ion diffusion and reducing local supersaturation; at the same time, the lithium-philic layer helps to form a stable deposition substrate, prevent dendrite growth, and ensure smooth and uniform lithium metal deposition, thereby improving the safety and cycle life of the battery.

[0037] Preferably, the above-mentioned lithium-philic nanoparticles include but are not limited to simple particles and oxides. Simple particles include Ag, Zn, Al, Ni and Se, etc., and oxides include CeO 2 、TiO 2 , ZnO, etc.

[0038] In some embodiments of the present invention, the above-mentioned sufficient dispersion is to add the lithium-philic nanoparticles into N-methylpyrrolidone (NMP) solution and magnetically stir for 4-6 hours.

[0039] In some embodiments of the present invention, the above drying is specifically to vacuum dry the lithium-philic nanoparticle solution coated on the copper foil at 60-70° C. for 12-16 hours. Preferably, the temperature is 65° C. and the vacuum drying time is 14 hours.

[0040] S2. Clean and preheat the surface of the lithium negative electrode.

[0041] By cleaning and preheating the negative electrode surface, the adhesion and uniformity of subsequent evaporation can be ensured.

[0042] S3. Transferring the lithium-philic nanoparticle layer onto lithium foil.

[0043] By transferring the lithium-philic nanoparticle layer to the lithium foil, the lithium ion deposition is uniformly guided, the irregular growth of lithium is reduced, the formation of dendrites is fundamentally inhibited, and the risk of short circuit caused by dendrites piercing the diaphragm is reduced. On the one hand, it can provide uniform nucleation sites: the surface of the lithium-philic nanoparticle layer has abundant active sites, which can significantly reduce the energy barrier of lithium metal nucleation, promote the deposition of lithium ions at uniformly distributed sites, and avoid dendrite growth caused by local oversaturation; on the other hand, it can improve the ion conduction path: the lithium-philic layer has high lithium ion conductivity, which can reduce the interface impedance and optimize the lithium ion migration path, thereby promoting the uniform deposition of lithium on the interface.

[0044] In some embodiments of the present invention, the above-mentioned transfer of the lithium-philic nanoparticle layer to the lithium foil is specifically to cover the copper foil on the lithium foil so that the lithium-philic nanoparticle layer is in contact with the lithium foil, and press a heavy object on the copper foil. After standing for 10-30 minutes, the copper foil is peeled off. At this time, the lithium-philic nanoparticle layer is transferred to the lithium foil.

[0045] Since the lithium foil has excellent ductility and adhesion to the lithium-philic nanoparticle layer, the lithium-philic nanoparticle layer can be peeled off from the copper foil.

[0046] Preferably, the weight may be a 1.5 kg metal disc.

[0047] S4. Evaporating the lithium foil to form a thin film (lithium-conducting homogeneous layer) on the surface of the lithium foil substrate.

[0048] The high density of inorganic materials enables them to form a dense protective barrier on the surface of the lithium metal negative electrode, effectively isolating the direct contact between lithium metal and the electrolyte, avoiding the decomposition of the electrolyte to produce gas or unstable byproducts, thereby significantly reducing the occurrence of side reactions. First, by evaporating high ionic conductivity materials, it is ensured that the artificial SEI layer has excellent lithium ion conductivity. Subsequently, the composite inorganic material is evaporated, which is composed of substances with high chemical stability, high mechanical properties and high ionic conductivity, giving the SEI layer multifunctionality. The composite evaporation of multiple inorganic materials can form grain boundaries, and the presence of grain boundaries provides a fast channel for lithium ion migration, further improving the conductivity of lithium ions, thereby optimizing the electrode interface performance. It also effectively isolates the direct contact between the lithium metal negative electrode and the electrolyte, significantly reducing the occurrence of side reactions, thereby improving the coulombic efficiency and reversibility of the battery.

[0049] In addition, through the optimized material evaporation process, a SEI layer with stable structure and uniform thickness is obtained, which not only improves the ion conductivity, but also reduces the interface impedance, ensuring excellent performance under long cycles. In addition, since the composite inorganic material layer is a composite of multiple materials, grain boundaries will be generated, further increasing the conductivity of lithium ions.

[0050] In some embodiments of the present invention, the above S4 includes the following steps:

[0051] S41, heating the high ion conductivity material to evaporate, placing lithium foil on the high ion conductivity material to perform a vapor deposition, and depositing a thin film on the surface of the lithium foil substrate.

[0052] In some embodiments of the present invention, the heating and evaporation parameters of the high ionic conductivity material are as follows: the vacuum degree is 10 -4 -10 -6 Pa, heating power is 230-270W, evaporation rate is Preferably, the vacuum degree is preferably 10 -5 Pa, the heating power is preferably 250W, and the evaporation rate is preferably

[0053] The lithium foil is placed 20-30 cm above the high ionic conductivity material.

[0054] S42, heating the inorganic composite material to evaporate, and placing the evaporated lithium foil on the inorganic composite material for secondary evaporation, so as to form a secondary thin film by deposition on the surface of the lithium foil substrate.

[0055] In some embodiments of the present invention, the inorganic composite material is made by mixing multiple inorganic materials. The inorganic materials include LiF, Li 2 O. Li 2 CO 3 , Li 3 N and Li 2 S. Preferably, the inorganic composite material is made by fully mixing three inorganic materials. The ionic conductivity material is preferably Li 3 Materials with low Li migration barriers such as N (Li migration barrier is 0.13 eV) and LiF (Li migration barrier is 0.17).

[0056] In some embodiments of the present invention, the heating and evaporation parameters of the inorganic composite material are as follows: the vacuum degree is 10 -4 -10 -6 Pa, heating power is 230-270W, evaporation rate is Preferably, the vacuum degree is preferably 10 -5 Pa, the heating power is preferably 250W, and the evaporation rate is preferably

[0057] The lithium foil is placed 20-30 cm above the inorganic composite material.

[0058] S5. Cool and solidify the lithium foil after the secondary evaporation to obtain a composite multifunctional lithium metal negative electrode.

[0059] After the film is formed, it can be firmly bonded to the substrate by cooling and solidification.

[0060] The present invention provides a composite multifunctional lithium metal negative electrode, which is prepared by any one of the above methods.

[0061] The present invention also provides the use of a composite multifunctional lithium metal negative electrode prepared by any of the above methods in battery materials.

[0062] Example 1

[0063] S1. First, the lithium-philic Ag nanoparticles were added to the NMP solution and magnetically stirred for about 5 hours to ensure sufficient dispersion; then, the dispersion was evenly coated on the copper foil using a coating rod and vacuum dried at 65°C for 14 hours to prepare a lithium-philic Ag nanoparticle layer.

[0064] S2. First, prepare a vacuum environment to ensure that evaporation is performed in an oxygen-free or extremely low-oxygen environment; then clean and preheat the negative electrode surface to ensure adhesion and uniformity of evaporation.

[0065] S3. Cover the lithium-philic Ag nanoparticle layer on the Li foil and place a metal disc with a mass of 1.5 kg on it; after standing for 20 minutes, use the ductility of the Li foil and its adhesion to the lithium-philic nanoparticles to make the nanoparticles adhere to the Li foil; then, peel off the Cu foil from the Li foil, and the nanoparticle layer will naturally transfer to the surface of the Li foil.

[0066] S4, evaporating the lithium foil to form a thin film on the surface of the lithium foil substrate:

[0067] S41. Fix the substrate with the nanoparticles transferred to it 25 cm above the crucible and place Li 3 N is added to the crucible in the vacuum chamber, and the temperature and evaporation rate of the heating source are controlled to make the material sublime and deposit on the substrate surface to form a thin film; the vacuum environment is 10 -5 Pa, the heating power of the crucible is 250W, and the evaporation rate is

[0068] S42, press LiF:Li 2 O:Li 2 CO 3 =1:1:1 fully mix the inorganic components to form a composite inorganic material, and add it to the crucible in the vacuum chamber; fix the substrate 25cm above the crucible, control the temperature and evaporation rate of the heating source, so that the material sublimates and deposits on the substrate surface to form a thin film; the vacuum environment is 10 -5 Pa, the heating power of the crucible is 250W, and the evaporation rate is

[0069] S5. After the film is formed, it is cooled and solidified so that the evaporated inorganic composite SEI material is firmly combined with the lithium substrate to obtain a composite multifunctional lithium metal negative electrode.

[0070] Example 2

[0071] This embodiment is basically the same as the embodiment 1, except that the lithium-philic nanoparticles are Zn.

[0072] Example 3

[0073] This embodiment is basically the same as the embodiment 1, except that the lithium-philic nanoparticles are Se.

[0074] Example 4

[0075] This embodiment is basically the same as the embodiment 1, except that the lithium-philic nanoparticles are ZnO.

[0076] Example 5

[0077] This embodiment is basically the same as embodiment 1, except that the inorganic components and ratios are LiF:Li 2 O:Li 3 N=1:1:1.

[0078] Example 6

[0079] This embodiment is basically the same as embodiment 1, except that the inorganic components and ratios are LiF:Li 2 O:Li 2 S=1:1:1.

[0080] Example 7

[0081] S1. First, the lithium-philic TiO 2 The nanoparticles were added to the NMP solution and magnetically stirred for about 4 h to ensure adequate dispersion; the dispersion was then evenly coated on a copper foil using a coating bar and vacuum dried at 60 °C for 12 h to prepare the lithiophilic TiO 2 Nanoparticle layer.

[0082] S2. First, prepare a vacuum environment to ensure that evaporation is performed in an oxygen-free or extremely low-oxygen environment; then clean and preheat the negative electrode surface to ensure adhesion and uniformity of evaporation.

[0083] S3, lithium-philic TiO 2 The nanoparticle layer is covered on the Li foil, and a metal disc with a mass of 2 kg is placed on it; after standing for 10 minutes, the nanoparticles are attached to the Li foil by utilizing the ductility of the Li foil and its adhesion to lithium-philic nanoparticles; then, the Cu foil is peeled off from the Li foil, and the nanoparticle layer is naturally transferred to the surface of the Li foil.

[0084] S4, evaporating the lithium foil to form a thin film on the surface of the lithium foil substrate:

[0085] S41, fix the substrate with the nanoparticles transferred to it 20 cm above the crucible, and place Li 3 N is added to the crucible in the vacuum chamber, and the temperature and evaporation rate of the heating source are controlled to make the material sublime and deposit on the substrate surface to form a thin film; the vacuum environment is 10 -4 Pa, the heating power of the crucible is 230W, and the evaporation rate is

[0086] S42, press LiF:Li 2 O:Li 2 CO 3 =1:1:1 fully mix the inorganic components to form a composite inorganic material, and add it to the crucible in the vacuum chamber; fix the substrate 20 cm above the crucible, control the temperature and evaporation rate of the heating source, so that the material sublimates and deposits on the substrate surface to form a thin film; the vacuum environment is 10 -4 Pa, the heating power of the crucible is 230W, and the evaporation rate is

[0087] S5. After the film is formed, it is cooled and solidified so that the evaporated inorganic composite SEI material is firmly combined with the lithium substrate to obtain a composite multifunctional lithium metal negative electrode.

[0088] Example 8

[0089] S1. First, lithium-philic CeO 2 The nanoparticles were added to the NMP solution and magnetically stirred for about 4 hours to ensure adequate dispersion; the dispersion was then evenly coated on a copper foil using a coating bar and vacuum dried at 70 °C for 16 hours to prepare the lithiophilic CeO 2 Nanoparticle layer.

[0090] S2. First, prepare a vacuum environment to ensure that evaporation is performed in an oxygen-free or extremely low-oxygen environment; then clean and preheat the negative electrode surface to ensure adhesion and uniformity of evaporation.

[0091] S3, Lithium-philic CeO 2 The nanoparticle layer is covered on the Li foil, and a metal disc with a mass of 2 kg is placed on it; after standing for 30 minutes, the nanoparticles are attached to the Li foil by utilizing the ductility of the Li foil and its adhesion to lithium-philic nanoparticles; then, the Cu foil is peeled off from the Li foil, and the nanoparticle layer is naturally transferred to the surface of the Li foil.

[0092] S4, evaporating the lithium foil to form a thin film on the surface of the lithium foil substrate:

[0093] S41, fix the substrate with the nanoparticles transferred to it 30 cm above the crucible, and place Li 3 N is added to the crucible in the vacuum chamber, and the temperature and evaporation rate of the heating source are controlled to make the material sublime and deposit on the substrate surface to form a thin film; the vacuum environment is 10 -6 Pa, the heating power of the crucible is 270W, and the evaporation rate is

[0094] S42, press LiF:Li2 O:Li 2 CO 3 =1:1:1 fully mix the inorganic components to form a composite inorganic material, and add it to the crucible in the vacuum chamber; fix the substrate 30cm above the crucible, control the temperature and evaporation rate of the heating source, so that the material sublimates and deposits on the substrate surface to form a thin film; the vacuum environment is 10 -6 Pa, the heating power of the crucible is 270W, and the evaporation rate is

[0095] S5. After the film is formed, it is cooled and solidified so that the evaporated inorganic composite SEI material is firmly combined with the lithium substrate to obtain a composite multifunctional lithium metal negative electrode.

[0096] Comparative Example 1

[0097] This comparative example is basically the same as Example 1, except that: no lithium-philic nanoparticles are used, steps S1-S3 are not performed, and no composite inorganic material is used in step S42, and the composite inorganic material is replaced by a single LiF.

[0098] Comparative Example 2

[0099] This comparative example is basically the same as Example 1, except that: no lithium-philic nanoparticles are used, steps S1-S3 are not performed, and step S42 does not use a composite inorganic material, and the composite inorganic material is replaced by a single Li 3 N.

[0100] Comparative Example 3

[0101] This comparative example is basically the same as Example 1, except that: no lithium-philic nanoparticles are used, steps S1-S3 are not performed, and step S42 does not use a composite inorganic material, and the composite inorganic material is replaced by a single Li 2 O.

[0102] Comparative Example 4

[0103] This comparative example is substantially the same as Example 1, except that no lithium-philic nanoparticles are used.

[0104] Experimental Example 1

[0105] The composite multifunctional lithium metal negative electrodes prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to performance tests to obtain capacity retention data after 500 cycles. The results are shown in Table 1; the ohmic internal resistance data are shown in Table 2. Figure 3 The interface impedance data results are shown in Figure 4 shown.

[0106] Performance test: In the button battery test, the negative electrode is the lithium negative electrode prepared in the embodiment or the comparative example, and the positive electrode is 12 mm in diameter and has an average load of about 2 mg cm -2 LiFePO 4 ) electrode, and the separator was polypropylene (PP). The battery was assembled in an argon-filled glove box and a carbonate-based electrolyte (1.0 mol L -1 LiPF 6 The solvent was ethyl carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. The charge and discharge tests were completed by a battery cycler, first performing 3 activation cycles at 0.2C, and then 1C (170mAg -1 ) rate test, the single charge and discharge time is fixed at 1 hour. The electrochemical impedance spectroscopy (EIS) test is carried out by an electrochemical workstation with a frequency range of 10 6 To 0.01Hz, the AC disturbance voltage amplitude is 5mV.

[0107] Table 1

[0108]

[0109]

[0110] From the data in Table 1, it can be seen that the capacity retention rate of the lithium negative electrode prepared in the embodiment of the present invention can reach more than 85% after 500 cycles, and has excellent cycle performance. However, the capacity retention rate of the comparative example is significantly lower than that of the embodiment of the present invention after 500 cycles. It can be seen that the present invention can improve the cycle performance, safety and overall efficiency of lithium batteries. Among them, the capacity retention rate of Example 1 is the highest. Comparing Examples 1-4, when the lithium-philic nanoparticles are Ag, the capacity retention rate is the highest; comparing Examples 1 and 5-6, when the inorganic components are LiF, Li 2 O and Li 2 CO 3 When , the capacity retention rate is the highest. Comparing Example 1 with Comparative Examples 1-3, it can be seen that using only a single inorganic substance and not using lithium-philic nanoparticles will lead to a significant decrease in the capacity retention rate.

[0111] observe Figure 3-4 After 200 cycles, the ohmic internal resistance and interface impedance of the embodiment are significantly lower than those of the comparative example, indicating that it has better electrochemical stability and interface compatibility during long cycles. The lower ohmic internal resistance reflects that the ion and electron transmission inside the battery is more efficient, while the smaller interface impedance indicates that the interface reaction between the lithium negative electrode and the electrolyte is less, and the side reaction is effectively suppressed. Overall, the embodiment significantly improves the cycle performance and energy conversion efficiency of the battery through optimized design, showing a more superior long-term operation capability.

[0112] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a composite multifunctional lithium metal negative electrode, characterized in that: The steps include: Adding lithium-philic nanoparticles into N-methylpyrrolidone solution, fully dispersing and coating on copper foil and drying, thereby obtaining a lithium-philic nanoparticle layer; Cleaning and preheating the surface of the lithium negative electrode; transferring the lithiophilic nanoparticle layer onto lithium foil; Evaporating the lithium foil to form a thin film on the surface of the lithium foil substrate; The evaporated lithium foil is cooled and solidified to obtain a composite multifunctional lithium metal negative electrode.

2. The method for preparing a composite multifunctional lithium metal negative electrode according to claim 1, characterized in that: The fully dispersed method is to add the lithium-philic nanoparticles into the N-methylpyrrolidone solution and stir magnetically for 4-6 hours.

3. The method for preparing a composite multifunctional lithium metal negative electrode according to claim 1, characterized in that: The drying is specifically to dry the lithium-philic nanoparticle solution coated on the copper foil under vacuum at 60-70° C. for 12-16 hours.

4. The method for preparing a composite multifunctional lithium metal negative electrode according to claim 1, characterized in that: The transfer of the lithium-philic nanoparticle layer to the lithium foil is specifically to cover the copper foil on the lithium foil so that the lithium-philic nanoparticle layer is in contact with the lithium foil, and to press a heavy object on the copper foil. After standing for 10-30 minutes, the copper foil is peeled off and the lithium-philic nanoparticle layer is transferred to the lithium foil.

5. The method for preparing a composite multifunctional lithium metal negative electrode according to claim 1, characterized in that: The evaporation deposition of lithium foil comprises: The high ion conductivity material is heated and evaporated, and a lithium foil is placed on the high ion conductivity material for a first evaporation deposition, so as to form a first film on the surface of the lithium foil substrate; The inorganic composite material is heated and evaporated, and the evaporated lithium foil is placed on the inorganic composite material for secondary evaporation, and a secondary thin film is deposited on the surface of the lithium foil substrate.

6. The method for preparing a composite multifunctional lithium metal negative electrode according to claim 5, characterized in that: The heating and evaporation parameters of the high ionic conductivity material are as follows: the vacuum degree is 10 -4 -10 -6 Pa, heating power is 230-270W, evaporation rate is 7. The method for preparing a composite multifunctional lithium metal negative electrode according to claim 5, characterized in that: The inorganic composite material is prepared by fully mixing a plurality of inorganic materials, and the inorganic materials include LiF, Li2O, Li2CO3, Li3N and Li2S.

8. The method for preparing a composite multifunctional lithium metal negative electrode according to claim 5, characterized in that: The heating evaporation parameters of the inorganic composite material are as follows: the vacuum degree is 10 -4 -10 -6 Pa, heating power is 230-270W, evaporation rate is 9. A composite multifunctional lithium metal negative electrode, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of a composite multifunctional lithium metal negative electrode prepared by the preparation method according to any one of claims 1 to 8 in battery materials.

Citation Information

Patent Citations

  • Preparation method for lithium ion supercapacitor taking stabilized lithium metal powder as negative electrode

    CN106449140A

  • Lithium negative electrode protective film, preparation method and lithium metal secondary battery

    CN109004276A

  • Composite negative electrode and preparation method and application thereof

    CN111430684A

  • Composite lithium metal negative electrode current collector as well as preparation method and application thereof

    CN112768697A

  • Metal lithium negative electrode and preparation method thereof

    CN118099366A

Cited By

  • Core-shell material, preparation method thereof and negative electrode material

    CN120901282A

  • Core-shell material, negative electrode material and preparation method thereof

    CN120901283A